Organized crime in Europe - von Lampe, Klaus (Henry Stewart Talks, 2008)
What is organized crime?, Patterns of organized criminal activities, Types of criminal structures: economic, social, and quasi-governmental, Mafia-like associations, Non-territorial secret societies, Family clans, Outlaw motorcycle gangs, Basic constellations of organized crime in Europe
Archived at 2022/04/03